2012
DOI: 10.1523/jneurosci.5086-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Two Seizure-Onset Types Reveal Specific Patterns of High-Frequency Oscillations in a Model of Temporal Lobe Epilepsy

Abstract: High-frequencyoscillations(HFOs;80 -500Hz)arethoughttomirrorthepathophysiologicalchangesoccurringinepilepticbrains.However,the distribution of HFOs during seizures remains undefined. Here, we recorded from the hippocampal CA3 subfield, subiculum, entorhinal cortex, and dentate gyrus to quantify the occurrence of ripples (80 -200 Hz) and fast ripples (250 -500 Hz) during low-voltage fast-onset (LVF) and hypersynchronous-onset (HYP) seizures in the rat pilocarpine model of temporal lobe epilepsy. We discovered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
153
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(174 citation statements)
references
References 42 publications
(28 reference statements)
18
153
1
1
Order By: Relevance
“…These two patterns may be the expression of the activation of the same networks, because the large-amplitude spikes typically detected in the hypersynchronous pattern are often followed by short runs of low-voltage fast activity (Perucca et al 2014). In line with the concept of the epileptic network, experimental work has shown that both patterns are generated by the limbic system in vivo in the pilocarpine model of mesial TLE (Levesque et al 2012), and in the in vitro whole guinea pig brain treated with different proconvulsive drugs, such as bicuculline or 4-aminopyridine (4AP) (Uva et al 2005;Carriero et al 2010;Boido et al 2014a).…”
Section: Seizure Onsetmentioning
confidence: 86%
See 2 more Smart Citations
“…These two patterns may be the expression of the activation of the same networks, because the large-amplitude spikes typically detected in the hypersynchronous pattern are often followed by short runs of low-voltage fast activity (Perucca et al 2014). In line with the concept of the epileptic network, experimental work has shown that both patterns are generated by the limbic system in vivo in the pilocarpine model of mesial TLE (Levesque et al 2012), and in the in vitro whole guinea pig brain treated with different proconvulsive drugs, such as bicuculline or 4-aminopyridine (4AP) (Uva et al 2005;Carriero et al 2010;Boido et al 2014a).…”
Section: Seizure Onsetmentioning
confidence: 86%
“…Evolving patterns are commonly observed in posttraumatic and poststroke epilepsy models (Pitkänen et al 2006;Kadam et al 2010), in models of mesial TLE either secondary to pharmacologically induced status epilepticus (Williams et al 2009;Bortel et al 2010;Levesque et al 2012), or induced by kindling (Michalakis et al 1998). As in humans, seizures in experimental animals with partial epilepsy occur randomly, often in clusters (Grabenstatter et al 2005;Goffin et al 2007;Williams et al 2009).…”
Section: Seizure Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bragin, Azizyan, Almajano, Wilson, and Engel (2005) have shown low‐voltage fast‐onset (LVF) and hypersynchronous‐onset (HYP) spikes preceding spontaneous seizures in freely moving rats that had SE‐induced kainic acid hippocampal injections. Levesque, Salami, Gotman, and Avoli (2012) demonstrated LVF and HYP in the rat pilocarpine model of TLE. Avoli and colleagues have recently studied the equivalent of LVF and HYP seizures in an in vitro slice preparation of rat perirhinal cortex (Köhling et al., 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Studies from animal models of epilepsy have revealed multiple sites where seizures begin such as amygdala (Bertram 1997), midline dorsal thalamus (Bertram, Mangan et al 2001), and parts of hippocampal formation (Lévesque, Salami et al 2012). …”
Section: Subiculum As New Site Of Injectionmentioning
confidence: 99%